Contribution to fundamental aspects of biophysics, radiobiology, and modeling of cellular response to low radiation doses - Belchior, Ana Lúcia Vital, 1979- (2014)
Tese de doutoramento, Engenharia Biomédica e Biofísica, Universidade de Lisboa, Faculdade de Ciências, 2014